High Pressure Stress Response: Involvement of NMDA Receptor Subtypes and Molecular Markers - Bliznyuk, Alice; Hollmann, Michael; Grossman, Yoram (Frontiers in Physiology, 2019)
Professional divers who are exposed to high pressure (HP) above 1.1 MPa suffer from high pressure neurological syndrome (HPNS), which is characterized by reversible CNS hyperexcitability and cognitive and motor deficits. HPNS remains the final major constraints on deep diving at HP. Prolonged and repetitive exposure to HP during deep sea saturation dives may result in permanent memory and motor impairment. Previous studies revealed that CNS hyperexcitability associated with HPNS is largely induced by N-methyl-D-aspartate receptors (NMDARs). NMDARs that contain the GluN2A subunit are the only ones that show a large (~60%) current increase at He HP. NMDAR subtypes that contain other GluN2 members show minor decrease or no change of the current. Immunoprecipitation was used in order to test the hypothesis that current augmentation may result from inserting additional NMDARs into the membrane during the 20–25 min compression. The results indicated that there is no increase in surface expression of NMDARs in the oocyte membrane under HP conditions. In contrast, consistent increase in glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and β-actin was discovered. GAPDH and β-actin are cytosolic proteins which involve in various cellular control processes, increase of their expression suggests the presence of a general cellular stress response to HP. Understanding the precise hyperexcitation mechanism(s) of specific NMDAR subtypes and other possible neurotoxic processes during HP exposure could provide the key for eliminating the adverse, yet reversible, short-term effects of HPNS and hopefully the deleterious long-term ones.